The relationship between moral intelligence and social intelligence with entrepreneurial self-efficacy - Seyed Ehsan Alavi; Masoumeh Ahmadi Shahwah (New Applied Studies in Management, Economics & Accounting, 2022)
The main purpose of this study is to investigate the relationship between moral and social intelligence with entrepreneurial self-efficacy. The statistical population of the study includes all male and female students of psychology in non-profit institutions of Khorasan Razavi province, 257 of whom were selected using random sampling method. The type of research method is correlation analysis and regression analysis. The collected information includes a 40-item questionnaire of moral intelligence, a questionnaire of social intelligence with 45 questions and questionnaire of entrepreneurial self-efficacy with 29 questions and a form of personal information of individuals whose data were analyzed by correlation analysis and regression. Findings show that there is a positive and significant relationship between moral intelligence and entrepreneurial efficiency and between social intelligence and entrepreneurial efficiency. Also, considering the significant regression of simultaneous study of entrepreneurial self-efficacy (as a dependent variable) with social and moral intelligence (as independent variables), at least part of entrepreneurial self-efficacy can be explained using emotional and moral intelligence. According to the research results and the role of moral and social intelligence in entrepreneurial efficiency, the higher the moral intelligence and the stronger the social connections, the higher the entrepreneurial efficiency.